EXPLORING THE DEVELOPMENT OF STUDENTS’ KNOWLEDGE OF CONVENTIONALISED SIMILES IN ENGLISH LEXICOLOGY AND PHRASEOLOGY: A COMPARATIVE STUDY - Hrdličková, Zuzana (Advanced Education, 2023)
Idioms are a colourful and fascinating aspect of English which are commonly used in all types of language, formal and informal, spoken and written. Despite the emerging theoretical accounts of idioms up to now, little attention has been paid to teaching and learning idiomatic expressions in English as a Foreign Language, English for Specific Purposes or English for Academic Purposes classroom. Developing idiomatic competence among English language learners in Slovakia remains a formidable challenge. Second-year undergraduates of the study programmes ‘Teacher Training of English Language and Literature’ (single major study) and ‘Teacher Training of English Language and Literature (double major study) need to master different types of idioms within one-term course in ‘English Lexicology and Phraseology’. Their language skills will increase rapidly if they can understand and use them confidently and correctly. The communication role of idiomatic comparisons is often neglected, as well. The aim of the paper is to find out their level of knowledge of standard idiomatic comparisons at the beginning and the end of the course. The paper intends to reveal how students of different nationalities – Slovak, Hungarian, Russian and Ukrainian – are able to explain the meaning of similes used in example sentences in English or their mother tongue. Altogether 51 students are tested twice via tests focused on similes, and their results are compared via a statistical t-Test. The results from the initial test show that their knowledge of idiomatic comparisons was not very wide. However, the results from the final test prove that they were motivated to learn idioms, and thus they extended their knowledge of idiomatic comparisons significantly. In addition, the paper suggests some implications for teaching and learning similes and phraseological units in general.